EFL Student’s Perception on Digital Learning Media Technology: The Case of Secondary School in Indonesia - Majid, Fattakhu Firli Dewi Nur; Rahman, Abd; Anwar, Saiful (FKIP Unismuh Makassar, 2025)
The development of digital technology has brought significant changes to the field of education, especially in the process of learning English. The use of digital learning media enables the delivery of materials to be more interactive, flexible, and engaging for students. This study aims to explore the perceptions of tenth-grade students at a secondary school in Banyuwangi, East Java, Indonesia, regarding the use of digital learning media in English language learning. Employing a qualitative case study approach, data were collected through classroom observations, semi structured interviews with 11 students, and questionnaires involving 30 participants. The findings, which were analyzed using thematic analysis for qualitative data and descriptive statistics for questionnaire results, indicate that the majority of students hold positive to very positive perceptions of digital media, particularly in terms of enhancing comprehension (average score 4.17) and making the learning process more engaging (average score 4.23). Classroom observations reinforced these results, showing that over 75% of students demonstrated active engagement when the teacher used interactive tools such as Quizizz, Wordwall, and YouTube-based instructional videos. Interviews revealed that digital media increases motivation and makes learning more enjoyable and interactive. Despite these benefits, the study also identified significant challenges, including limited device availability, unstable internet connectivity, and insufficient teacher guidance in using digital media. Approximately 20% of students showed passive behaviour or lacked confidence in technology based learning environments. Students also expressed the need for additional teacher training, the provision of stable Wi-Fi, and more structured and varied digital-based assignments. This study emphasizes that the successful integration of digital media in English learning relies heavily on adequate infrastructure, teacher readiness, and inclusive instructional strategies. These findings contribute valuable insights for educational policy and practice in the digital era, offering recommendations to improve digital literacy, professional development for educators, and equitable access to technological resources for all students